Vérification :
A = (3x - 5)² - (4x + 8)(1 - x)
A = 9x² - 25 - 4x -4x² + 8 - 8x
A = 5x² -12x -17

B= (2x - 4)(2x + 4) + (2x - 4)(3 - 7x)
B= 4x² + 8x - 8x -16 + 6x -14x² -12 + 28x
B = -10x² +34x -28

C= (1 -4x)² - (7 + 5x)²
C= 1 - 16x² - 49 - 25x²
C= -41x² -48


D= 12x² -3(5x + 7) +20x
D = 12x² -15x - 21 + 20x
D= 12x² +5x -21

1

Réponses

2013-12-18T22:37:19+01:00
A = (3x - 5)² - (4x + 8)(1 - x)
=9x²-30x+25-(4x-4x²+8-x)
=9x²-30x+25-4x+4x²-8+x
=13x²-33x+17

B= (2x - 4)(2x + 4) + (2x - 4)(3 - 7x)
=4x²-16+6x-14x²-12+28x
=-10x²+34x-28

C= (1 -4x)² - (7 + 5x)²
=1-8x+16x²-(49+60x+25x²)
=1-8x+16x²-49-60x-25x²
=-9x²-68x-48

D= 12x² -3(5x + 7) +20x
=12x²-15x-21+20x
=12x²+5x-21